Experimental Investigation of Ingavirin® Antiviral Activity Against Human Parainfluenza Virus - V. V. Zarubaev; V. Z. Krivitskaya; V. E. Nebolsin; O. I. Kiselev (Антибиотики и Химиотерапия)
The Ingavirin® antiviral properties with respect to the parainfluenza virus, as an actual human respiratory tract pathogen, were investigated by two methods, i.e. immunoenzymatic analysis and microtetrazolium test. The results showed that along with the immediate antiviral activity Ingavirin® had nonspecific cytoprotective properties. While affecting the virus proteins synthesis, Ingavirin® lowered the virus cytopathogenic action. The drug significantly decreased the portion of the bronchial epithelium cells killed at the stage of acute infection.